Carborane-based carbonic anhydrase inhibitors - Brynda, Jiří; Mader, Pavel; Šícha, Václav; Fábry, Milan; Poncová, Kristýna; Bakardiev, Mario; Grüner, Bohumír; Cígler, Petr; Řezáčová, Pavlína (Angewandte Chemie (International ed. in English), 2013)
CA inhibitors: Human carbonic anhydrases (CAs) are diagnostic and therapeutic targets. Various carborane cages are shown to act as active-site-directed inhibitors, and substitution with a sulfamide group and other substituents leads to compounds with high selectivity towards the cancer-specific isozyme IX. Crystal structures of the carboranes in the active site provide information that can be applied to the structure-based design of specific inhibitors.
Keywords: Drug Design; vztahy mezi strukturou a aktivitou; drug discovery; Structure-Activity Relationship; inhibitory karboanhydras; lidé; Carbonic Anhydrase Inhibitors; structure elucidation; racionální návrh léčiv; objevování léků; carbonic anhydrases; carboranes; inhibitors; Drug Discovery; Humans